PPP 기반 항법 알고리즘을 이용한 파고 계측시스템 설계 및 구현 - 송세필; 조득재; 박슬기; Song, Se Phil; Cho, Deuk Jae; Park, Sul Gee (한국정보통신학회논문지, 2015)
A GPS based wave height meter system is proposed in this paper. The proposed system uses a dual-frequency measurements, a precise GPS satellite information and a PPP-based navigation algorithm to estimate the position with high accuracy. This method does not need to receive corrections from the reference stations. Therefore, unlike RTK based wave meter, regardless of the distance to the reference stations, it is possible to estimate position with high accuracy. This system is very simple and accurate system, but accelerometer-based system requires the other sensors such as GPS. Because position error is accumulated in the accelerometer system and must be removed periodically for high accuracy. In order to get the measurements and test the proposed wave height meter system, a buoy equipped with the test platform is installed on the sea near by Jukbyeon habor in Uljin, Korea. Then, to evaluate the performance, compares built-in commercial wave height meter with proposed system. 본 논문에서는 GPS 위치 정보를 이용한 파고계측시스템을 제안한다. 제안한 시스템은 이중주파수 측정치 및 GPS 정밀위성정보를 이용하여 위치를 추정하는 PPP 기반 항법 알고리즘을 사용한다. 이를 이용하여 기준국으로부터 보정정보를 받는 RTK나 DGPS 기반 파고계와 달리 기준국과의 거리에 관계없이 높은 정확도로 위치 추정이 가능하다. 그리고 GPS 단독으로 운용되는 간단한 시스템이므로, 가속도계 기반 파고 계측 시스템처럼 다른 센서를 이용하여 누적되는 위치 오차를 보정할 필요가 없다. 제안한 파고계측시스템을 테스트하기 위하여 경북 울진 죽변항 인근 해역에 제안한 시스템과 기상청에서 활용하는 상용 파고계를 탑재한 부표를 설치하고, 시험 운용하였다. 그리고 부표로부터 전송된 두 가지 파고 데이터를 상호 비교함으로써 제안한 시스템의 성능을 평가하였다.